2006
DOI: 10.1007/s10157-005-0401-8
|View full text |Cite
|
Sign up to set email alerts
|

Para-capillary electron-dense deposits reduce glomerular filtration in patients with primary glomerular diseases

Abstract: PCEDD significantly affected FF levels in patients with primary glomerular diseases. FF may not be an accurate indicator of intraglomerular blood pressure in patients with overt PCEDD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…46 Hence, the proliferation of extracellular matrix may be aggravated by the CsA in IMN patients with an FSGS lesion. The hydraulic permeability of the glomerular capillary walls is likely depressed by paracapillary electron-dense deposits, 47 basement membrane thickening and foot process broadening, 48 and increases of the ltration surface area and net pressure for ultra ltration are observed. In a study done by Gupta, the glomerulus was found to be enlarged in IMN patients with FSGS lesions; this nding supported the hypothesis of glomerular hyper perfusion as a cause of the development of FSGS in IMN.…”
Section: Discussionmentioning
confidence: 99%
“…46 Hence, the proliferation of extracellular matrix may be aggravated by the CsA in IMN patients with an FSGS lesion. The hydraulic permeability of the glomerular capillary walls is likely depressed by paracapillary electron-dense deposits, 47 basement membrane thickening and foot process broadening, 48 and increases of the ltration surface area and net pressure for ultra ltration are observed. In a study done by Gupta, the glomerulus was found to be enlarged in IMN patients with FSGS lesions; this nding supported the hypothesis of glomerular hyper perfusion as a cause of the development of FSGS in IMN.…”
Section: Discussionmentioning
confidence: 99%
“…In MN, subepithelial immune deposits may tamper with podocyte attachment to the glomerular basement membrane [ 10 ], and promote the formation of FSGS lesions. The hydraulic permeability of the glomerular capillary walls may be reduced by the epithelial immune complex [ 29 ], basement membrane thickening, and foot process broadening [ 30 ]. Subsequently, increases in the filtration surface area and net pressure for ultrafiltration are observed.…”
Section: Discussionmentioning
confidence: 99%